Kegiatan Bercocok Tanam untuk Anak Usia Dini dalam Local Wisdom Outing Class di Eduwisata Ndalem Kerto - Pujiati, Ayu; Wulansari, Betty Yulia (Insititut Agama Islam Negeri (IAIN) Curup, 2023)
Naturalist intelligence is the ability to love the beauty of nature which can be stimulated through observing the environment, farming, raising animals, and sensitivity to natural phenomena. Through the stimuli provided, it is hoped that children will become the next generation who have environmentally friendly characters and have the awareness to protect and preserve the existing environment. Through farming activities, it can create a feeling of love for the natural surroundings and can develop children's naturalist intelligence. This article aims to find out the benefits obtained from farming activities in the local wisdom outing class at Eduwisata Ndalem Kerto. This article uses a qualitative descriptive research method. For data collection techniques, this article uses observation and literature study techniques. Based on the results of this research, it can be concluded that the local wisdom outing class activities at Eduwisata Ndalem Kerto have many benefits. The benefits of this activity can improve aspects of children's development, such as aspects of naturalist intelligence, language aspects, motor aspects and social-emotional aspects of children.